NURSE PERCEPTIONS TO IMPLEMENT FIVE MOMENTS OF HAND WASHING - Zuliani, Zuliani (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: Hand washing is one of the actions to clean hands and fingers to reduce nosocomial infections. Correct and appropriate nurse’s behavior in carrying out hand washing determines the adequate hand washing. Objective: This study purpose was to determine the perceptions of the nurse to implement five moments of hand washing. Methods: The study design used a description. Sampling used in this study was 20 respondents. The perceptions were measured by questionnaire. The statistical test data was analyzed using univariate. Results: The study results showed that the majority of respondents had a good perception (75%), while a small number of respondents had a fairly good perception (25%). Conclusion: The nurse's perception of carrying out the five moments of hand washing in the emergency room at Unipdu Medika Hospital was good. Hence, doing the correct hand washing procedure can prevent nosocomial infections.